The Fiddlers of James Bay: Transatlantic Flows and Musical Indigenization among the James Bay Cree - Wilkins, Frances (MUSICultures, 2013)
Fiddle music and dancing have formed a major component of the social lives of the Algonquian First Nations Cree population living in the James Bay region of Ontario and Québec since the instrument and its associated repertoire were introduced to the region by British (and most notably Scottish) employees of the Hudson’s Bay Company who travelled across the Atlantic on ships from the late 17th to the 20th century. Based on archival research and ongoing fieldwork in the region since 2011, this article aims to explore this transatlantic musical migration from the British Isles to James Bay and the reshaping of Scottish fiddle music and dance through indigenization and incorporation into the Cree cultural milieu. By examining this area of cultural flow, the article seeks to engage with current themes in ethnomusicology on the subject and add to the growing body of knowledge surrounding them.